Uniqueness of the SRB measure for piecewise expanding weakly coupled map lattices in any dimension - Keller, Gerhard; Liverani, Carlangelo (Communications in Mathematical Physics, 2006)
We prove the existence of a unique SRB measure for a wide range of multidimensional weakly coupled map lattices. These include piecewise expanding maps with diffusive coupling.